COPD RISK IN PAKISTANI PUNJABI POPULATION: ROLE OF GATM, PSMA4, AND CHRNA5-A3-B4 GENE VARIANTS - Samra Kousar; Atif Mahmood; Mohsin Sajjad; Atia Rehman; Ujala Tayyab; Ayesha Shahbaz Khan; Mariam Shahid (International Journal of Pharmacy & Integrated Health Sciences)
Background: Chronic obstructive pulmonary disease (COPD) is a complex, multifactorial and polygenic disease concerning genetic and environmental factors. Objectives: The selected single nucleotide polymorphisms (SNPs) within or between potential candidate genes were studied to find the association with the onset of COPD disease in the Punjabi population of Pakistan. Methods: 254 COPD patients and 219 control subjects were enrolled for this case-control study. After a literature review and with the help of bioinformatics tools, risk-associated deleterious SNPs residing within or among genes GATM, PSMA4, CHRNA3, CHRNA5, and CHRNB4 were selected to evaluate their association with COPD. Following the mini-sequencing technique, the disease’s association analysis was done using PLINK v1.9 and SHEsis Plus. Results: The mean age of cases was 48.9 ± 9.04 years (N=254), comprising 55.1% males and 44.9% females with 36.6% positive family history of COPD. ‘C’ alleles for rs200551904, rs199547652 and rs1288775 are associated with COPD (p-value 9.70x10-9, 1.14x10-5 and 7.45x10-4 respectively), whereas the ‘CC’ genotype of rs8053 seems to be a protective factor for the disease. The variants rs1288775 and rs199547652 remained associated even with adjusting results for smoking exposure (p-value 0.002 and 1.22 x10-6, respectively). Haplotype analysis for rs1145086, rs1288775, rs8053, rs77994111, rs16969968, rs200551904, rs199547652, rs19968256, and rs181037724 shows that four of the haplotypes H4, H9, H10 and H14, (GATAGGACC; CACAAGACC; CATAGGACC; GACAAGACC respectively), are associated with the disease, while two haplotypes, H1 and H11 (CACAGGCCC and CGCAGGACC respectively), are protective factors against the disease. Conclusion: The association of COPD with chromosome 15 variants in the Punjabi population is reported in this study.